Cerebral proliferative angiopathy. (20th September 2011) - Marks, Michael P; Steinberg, Gary K
Abstract : Cerebral proliferative angiopathy is a rare lesion marked by diffuse intravascular shunting, which should be differentiated from brain arteriovenous malformations. A patient is presented with cerebral proliferative angiopathy and documented progressive development of hypervascular shunting involving extensive portions of the left hemisphere. The patient had angiographic and laboratory evidence of angiogenesis and a progressive neurologic deterioration which corresponded to the development of her lesion. This is the first case which documents the progressive proliferative changes seen with this abnormality.